Choosing your Surgeon Wisely: Using Provider-Procedure-Volume-Specific Data for Informed Choice - Weeks, Bill; Segundo, Bruno Demuro; Lee, Dan M; Michael, Divya; Weinstein, James; Lavista Ferres, Juan M. (Journal of Community Medicine & Public Health, 2024)
Background: There is a longstanding association between provider-specific procedure volumes and outcomes. “To inform patients and caregivers about clinicians’ experience,” the Centers for Medicare and Medicaid Services (CMS) recently released datasets on procedure- and provider-specific volumes for twelve procedures provided to Traditional Medicare and Medicare Advantage enrolees in 2021. We sought to determine the utility of these datasets for consumers’ informed decision making. Methods: Conducting a retrospective analysis of those datasets, we assigned proceduralists to procedure-specific volume quintiles, and, for each procedure and volume quintile, calculated the mean number of procedures performed, the number and specialties of providers performing them, and, at the hospital-referral region (HRR) level, the number of each procedure performed per 100,000 Medicare enrolees and the proportion of specified-procedure-providing proceduralists in the highest volume quintiles. Results: A substantial amount of data processing was necessary to merge relevant files and identify reasonable primary proceduralist specialties. Narrowing our analysis to that subset, we found considerable procedure specific variation in the mean number of procedures performed and the number of high-volume proceduralists per 100,000 Medicare enrolees. When a specialist performed multiple procedure types, excepting orthopaedic surgeons, performing a greater number of procedure types was associated with lower likelihood of being in the top volume quintile. Conclusions: While CMS surfaced these datasets to help inform consumers, the data are complex and require a substantial amount of data manipulation to be informative. To improve consumer friendliness, CMS might identify high-volume proceduralists on its “Find & compare providers near you” tool.